Strategi Guru PAI dalam Membudayakan Nilai-Nilai Agama pada Peserta Didik di SDN Banjarmlati 1 Kediri - Umam, Mohamad Choirul (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
Because the globalization age has many affects in aspects of life, especially in the field of education, the teachers of Islamic religion's education (PAI) have devised a strategy to cultivate the values of religion in the globalization era. As a country where Islam is the majority religion, Islamic education should be the cornerstone of education for Indonesian society. PAI instructors have a critical role in instilling religious values in students, and this applies to all students. Cultural values may be instilled by the teacher since they play a vital role in setting an example for students. The students are concerned about religion, but they require cultural support in order for religious ideals to be incorporated in everyday life. This example will be appealing to researchers interested in nurturing religious ideals in "SDN Barjarmlati 1 Kediri." Hablum Min Allah (relation with Allah), which is exemplified by participating in ubudiyah activities such as congregational dhuhur prayer, congregational dhuha prayer, and BTQ (read and write Qur'an), and Hablum Minannas (relation with human), which is exemplified by helping one another when one of the school residents suffers a disaster by attending infaq held at school every Friday. Hablum minal alam (relations with nature), which is a call to keep the surrounding environment, particularly schools, clean.